Interplay of the Macroeconomy and Real Estate: Systematic Review of Literature - Kwakye, Benjamin; Haw, Chan Tze (International Journal of Economics and Financial Issues, 2020)
This research systematically reviews and evaluate literature on the interplay of the macroeconomy and house prices in the contemporary. The research recapitulates the ï¬ndings, data and models between and among the discussants in the extant literature to unearth new research gaps. The study analyzed 64 papers from thousands of scholarly papers from purposively sampled reputable database from 2015 to March, 2020, using a systematic review methodology. Based on the inclusion and exclusion criteria, the selected papers were categorized in relation to the direction of the impact to showing the nexus on the topic. It found that: both the macroeconomy and house prices impact on each other. However, macroeconomic variables were noted to impact on house prices more frequently than the opposite. To the best of the authors knowledge, this review is the first in recent past, to unembellished the dynamic relationship between the macroeconomy and house prices based on the direction in the contemporary. Particularly in the era where there are so much conjectures in the market of another financial crises. The study makes a contribution by identifying new research opportunities for future research and has practical implications to policy makers, researchers and property investors. Keywords: Macroeconomy, house prices, housing market, review. JEL Classifications: E, O18 DOI: https://doi.org/10.32479/ijefi.10368